2015
DOI: 10.3349/ymj.2015.56.2.382
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Not Associated with Increased Operative Complications in Single-Site Robotic Partial Nephrectomy

Abstract: PurposeTo evaluate the impact of high body mass index (BMI) on outcomes following robotic laparoendoscopic single-site surgery (R-LESS) robotic-assisted laparoscopic partial nephrectomy (RPN).Materials and MethodsData from 83 Korean patients who had undergone robotic partial nephrectomy from 2006 to 2014 were retrospectively analyzed. The subjects were stratified into two groups according to WHO definitions for the Asian population, consisting of 56 normal range (BMI=18.5-24.99 kg/m2) and 27 obese (≥25 kg/m2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Our results show no statistically significant difference in intraoperative complications between the BMI groups, and this finding is compatible with other studies [32–34]. Despite the common assumption of higher intraoperative blood loss and blood transfusion rates in obese patients [35], our study illustrated that blood transfusion requirements tended to be higher among patients with BMI <25 as compared to BMI >30 kg/m 2 .…”
Section: Discussionsupporting
confidence: 91%
“…Our results show no statistically significant difference in intraoperative complications between the BMI groups, and this finding is compatible with other studies [32–34]. Despite the common assumption of higher intraoperative blood loss and blood transfusion rates in obese patients [35], our study illustrated that blood transfusion requirements tended to be higher among patients with BMI <25 as compared to BMI >30 kg/m 2 .…”
Section: Discussionsupporting
confidence: 91%
“…Several analyses have demonstrated that although obesity may pose unique intraoperative challenges, it does not necessarily lead to an increased complication rate in RPNs. In particular, Kiziloz and associates, 25 Komninos and colleagues, 26 and Abdullah and colleagues, 21 each of which encompassed several prior single institution studies, did not demonstrate an increased complication rate. These data suggest equivalent outcomes in terms of length of stay, complication rate, and positive margin rates.…”
Section: Discussionmentioning
confidence: 92%
“…However, several studies have demonstrated the feasibility of performing nephron-sparing surgery or utilization of minimally invasive techniques in obese patients without any significant adverse outcomes when compared with non-obese patients. [24][25][26] Currently, criteria to decide whether a patient is a candidate for nephron-sparing surgery versus radical nephrectomy is based on tumor characteristics and not on BMI. The association between BMI and radical nephrectomy in this study probably reflects the academic setting of our institution where challenging cases are routinely referred.…”
Section: Discussionmentioning
confidence: 99%